Report on Zimbabwe living landscape engagements - Matangi, Dorcas; Chimonyo, Vimbayi Grace Petrova (CIMMYT, 2025)
This report synthesises insights from the Quarter 2 (June 2025) and Quarter 4 (October 2025) meetings of the Mbire Natural Resources and Agriculture (NRA) Committee and interprets them through the lens of the Mbire District as a Living Landscape. The CGIAR Multifunctional Landscapes (MFL) Program views the district landscape as a dynamic socio-ecological system where environmental change, resource-use pressures, wildlife interactions, governance processes, and human decision-making continuously interact. Within this Living Landscape, the NRA Department of the Mbire Rural District Council serves as the central coordination mechanism through which the district observes, interprets, and responds to landscape signals. Through its quarterly committee system, the NRA convenes government agencies, development organisations, private actors, and community representatives to collectively assess ecological conditions, prioritise interventions, and negotiate responses to emerging challenges. For the MFL Program, the NRA meetings provide a structured entry point into the Living Landscape, enabling realtime observation of ecological stressors, institutional capacities, and community experiences. The Q2 and Q4 meetings held during distinct seasonal periods offer complementary insights into how land-use patterns, wildlife behaviour, forest conditions, and natural resource pressures shift across the year. The analysis demonstrates that Mbire’s landscape is under increasing pressure from gully erosion, woodland loss, fire outbreaks, and human wildlife conflict, with many issues intensifying between June and October. It also shows that the NRA governance system, while collaborative and responsive, faces operational constraints that limit effective action. For MFL, the combined insights reveal clear opportunities for co-developing innovations aligned with AoW1 priorities, including regenerative land restoration, wildlife-sensitive agriculture, nutrition-sensitive food systems, and strengthened coordination mechanisms.